TRANSFORMASI SOSIAL BUDAYA NGOPI DI KOTA PEKANBARU (STUDI DI KEDAI KOPI MEGARIA DAN COFFEE SHOP BOCO KOPI) - Pangestu, Bimo Teguh; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The coffee shop is a space where coffee culture was first born and developed, which was initially only carried out by adults and dominated by men. Modern with various facilities and a variety of drinks offered for various circles. As one of the public spaces where coffee culture develops and not only buying and selling activities are there, but there are activities to exchange information or spend time while enjoying coffee alone or with friends. Coffee culture is not only a phenomenon among adults, however the phenomenon of coffee culture also occurs among young people as a space that gives rise to various activities or lifestyles that are influenced by modernist values. This research aims to find out how the coffee culture is before and after the social transformation at the Megaria Coffee Shop and Coffee Shop Boco Kopi. The selection of research subjects was carried out by accidental samples. This study uses a descriptive qualitative research method. Based on the results of the study, coffee culture has existed for a long time in coffee shops, such as the Megaria coffee shop. Then with the development of science and technology, people's needs increase, especially in the coffee industry, this stimulates coffee industry activists to develop in the coffee shop space so that coffee shops with a more modern concept emerge modern as Coffee Shop Boco Kopi. Keywords: Social Transformation, Coffee Culture, Hanging Out, Coffee Shops, Lifestyle